Pemikiran Tafsir Djohan Effendi - Faizin, Hamam; Kesuma, Arsyad Sobby (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
This article is a content research on the book “Pesan-pesan al-Qur’an Mencoba Mengerti Intisari Kitab Suci” (The messages of Qur’an: an effort to understand the nutshell of Sacred Book) by Djohan Effendi (2012). It overviews the background and motive of writing this book (Pesan-pesan al-Qur’an/PPQ), Qur’anic exegesis methodology and presentation and also reveals the advantages and shortcomings of PPQ. PPQ is Djohan Effendi’s effort to comprehend the messages of Qur’an. PPQ is not aimed at academic interest, so PPQ is free form the established methodology of Qur’anic exegesis. PPQ contains the global interpretation of 114 surahs of Qur’an, appendix on thematics interpretation and poetical rendering of al-Fatihah and Juz Amma. The exegisis by reason is used in PPQ and ijmali (global) and maudu’i (thematic) are the method of presentation of PPQ. In addition, PPQ has moral-ethics (adabi) and ijtima’i (society/community) by stressing to the substantial and universal values. PPQ is completed with the poems in every closing of interpreting Surah and attached the poetical translation of Juz Amma and Surah al-Fatihah. Regardless of its uniqueness and lacks, PPQ as a part of Indonesia Qur’anic interpretation deserves to be appreciated.